Characterization of bone cements prepared with either hydroxiapatite, α-TCP or bovine bone - Vargas - Coronado, R. F.; Chan - Chan, L. H.; Cervantes - Uc, J. M.; Cauich - Rodríguez, J. V.; Piña - Barba, M. C. (Revista Mexicana de Ingenieria Biomedica, 2013)
In this work, we report the preparation of bone cement by using methyl methacrylate (MMA) as a base monomer and either hydroxyapatite (HA), alpha-tricalcium phosphate (α-TCP) or bovine bone particles as bioactive fillers. In general, it was observed that curing times increased by the addition of any of these fillers (from 4 to 6.7 min). Maximum temperatures decrease slightly by the addition of 20 wt.% of either α-TCP or bovine bone (80.3ºC and 73.2ºC respectively) but it did not change by the addition of HA (84.3ºC) with respect to PMMA only bone cement used as a control. Residual monomer content was lower than 4% in the bioactive bone cement. By using α-TCP or bovine bone compressive strength increased with respect to the unfilled bone cement but it was reduced when HA was used. However, all these formulations fulfill the 70 MPa required for bone cement use. Flexural strength was increased by using either α-TCP o bovine bone but the addition of HA decreased this property compared to the base bone cement. However, the minimum flexural strength (50 MPa) was fulfilled only in those experimental formulations containing low amounts of α-TCP. The minimum tensile strength (30 MPa) was satisfied by all formulations but it was always lower than the exhibited by the unfilled bone cement.